18th and Arkansas Housing
Se desarrolla la obra a cargo de David Baker Associates.
Keywords: DAVID BAKER & PARTNERS; BAKER, DAVID; ESTADOS UNIDOS; CALIFORNIA; SAN FRANCISCO; EDIFICIOS DE VIVIENDAS; VIVIENDAS ADOSADAS